SEMESTER IN MALAYSIA: A USM EDUCATIONAL EXPERIENCE NOT TO BE MISSED - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 15 February 2016 – Universiti Sains Malaysia (USM) recently hosted 10 undergraduates from Gustavus Adolphus College (GAC), Minnesota, USA as the result of a collaboration which has been established earlier on between the two institutions.